EXCELLENT registry: a prospective, multicenter, global registry of endovascular stroke treatment with the EMBOTRAP device - Nogueira, Raul G.; Andersson, Tommy; Haussen, Diogo C.; Yoo, Albert J.; Hanel, Ricardo A.; Zaidat, Osama O.; Hacke, Werner; Jovin, Tudor G.; Fiehler, Jens; De Meyer, Simon F.; Brinjikji, Waleed; Doyle, Karen M.; et al. (Stroke, 2024)
BACKGROUND: The EXCELLENT registry aimed to evaluate the effectiveness of the EMBOTRAP Revascularization Device in an all-comer population in a real-world setting, with a focus on the composition of retrieved clots. - METHODS: EXCELLENT is a prospective, global registry of patients with acute ischemic stroke treated with EMBOTRAP as the first-line mechanical thrombectomy device conducted at 34 sites (25 sites contributing clot) from September 2018 to March 2021, utilizing core imaging and central histology laboratories blinded to clinical data, independent 90-day modified Rankin Scale assessment and Clinical Events Committee. - RESULTS: After screening 3799 patients, a total of 997 subjects (mean age, 70.0±14.2 years; 51.8% women; 19.7% non-White) were included. The first-pass modified Treatment in Cerebral Infarction (mTICI) ≥2b rate was 64.5% (623/966), first-pass mTICI ≥2c was 39.1% (378/966), and final mTICI ≥2b was 94.5% (931/985). A total of 427/912 (46.8%) patients achieved a 90-day modified Rankin Scale of 0 to 2 or ≤baseline. Embolization to a new territory occurred in 0.2% (2/984), and symptomatic intracranial hemorrhage at 24 hours in 1.6% (16/997). The 90-day mortality was 19.1% (175/918). Device- and/or procedure-related serious adverse events occurred in 5.9% (54/912) through 90 days. The mean RBC percentage of retrieved clots was 45.62±21.372. Among patients who achieved mTICI ≥2b with the first pass, 15.7% (52/331) and 9.7% (32/331), respectively, had RBC-poor (<25%) and RBC-rich (>75%) clots. Patients with no clot retrieved in any procedural pass had a lower percentage of hyperdense or susceptibility vessel sign on baseline imaging (58.9% versus 74.7%; P<0.001), pointing to a potential preprocedure indicator of challenging clot. - CONCLUSIONS: The EXCELLENT registry informs real-world practices in mechanical thrombectomy and sheds light on the range of clots effectively retrieved by current technology. This is the first report of detailed patient characteristics where mechanical thrombectomy maneuvers failed to remove any clot material. Although the composition of nonretrievable clots cannot be assessed histologically, the results support the notion that no retrieval may be correlated with imaging findings suggesting clots lower in RBC. - REGISTRATION: URL: https://www.clinicaltrials.gov; Unique identifier: NCT03685578.